1987
DOI: 10.1104/pp.85.4.902
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Metabolism of a Sucrose Analog (1′-Fluorosucrose) into Zea mays L. Endosperm without Invertase Hydrolysis

Abstract: ABSTRACr l'-Fluorosucrose (FS), a sucrose analog resistant to hydrolysis by invertase, was transported from husk leaves into maize (Zea mays L., Pioneer Hybrid 3320) kernels with the same magnitude and kinetics as sucrose. "C-Label from I"CqFS and l"lqsucrose in separate experiments was distributed similarly between the pedicel, endosperm, and embryo with time. FS passed through maternal tissue and was absorbed intact into the endosperm where it was metabolized and used in synthesis of sucrose and methanol-chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…Similarities between results obtained in maize and sugarcane led to the general view that the described sequence of events proceeded the same way in many tissues. More recent histochemical studies of invertase in maize tissues have confirmed earlier localizations (8), but sucrose hydrolysis no longer appears essential for all sucrose import into kernels (29) or many other sink structures (15). Likewise, the extent of sucrose breakdown and activity of associated enzymes during sucrose import is now believed to vary considerably.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Similarities between results obtained in maize and sugarcane led to the general view that the described sequence of events proceeded the same way in many tissues. More recent histochemical studies of invertase in maize tissues have confirmed earlier localizations (8), but sucrose hydrolysis no longer appears essential for all sucrose import into kernels (29) or many other sink structures (15). Likewise, the extent of sucrose breakdown and activity of associated enzymes during sucrose import is now believed to vary considerably.…”
mentioning
confidence: 89%
“…Earlier studies have clearly demonstrated the importance of acid invertase during assimilate transfer into immature sugarcane stems (13,14) and developing corn kernels (30). However, sucrose hydrolysis later was found not to occur during photosynthate entry into a variety of other sink tissues ( 16 and references cited therein, 29). In grapefruit, the capacity of both soluble and insoluble acid invertases drops to very low levels in tissues still rapidly accumulating dry matter.…”
Section: Comparative Activities Of Sucrose-metabolizing Enzymesmentioning
confidence: 99%
“…Sink systems vary in the extent to which they hydrolyze imported sucrose, but data from maize (29) and other species (4,22) now indicate that although cleavage and resynthesis may occur, it does not appear essential for transport. Citrus results reported here are consistent with this hypothesis.…”
Section: Sucrose Hydrolysismentioning
confidence: 99%
“…Short-term experiments with excised kernels showed passive sugar uptake (10), but neither sustained incorporation of external sugars into starch nor kernel growth has been shown with that experimental system. Although sucrose is hydrolyzed before or during uptake, this hydrolysis does not appear to be essential for sucrose movement into the endosperm (20). Thus, the contribution of invertase to the transport process is uncertain, and the mechanism of sugar transport into intact endosperm and its possible regulation is unclear.…”
mentioning
confidence: 99%